PENGARUH PERENCANAAN PAJAK YANG DIPROKSIKAN DENGAN EFFECTIVE TAX RATE (ETR) DAN BOOK TO TAX DIFFERENCE (BTD) TERHADAP NILAI PERUSAHAAN: (Studi Empiris: Perusahaan Pertambangan Yang Terdaftar di Bursa Efek Indonesia (BEI) Periode 2022-2024) - Anggriani, Luvi; Ramadhanni, Nazwa Safina; Apriliani, Alma (Jurnal Maneksi (Management Ekonomi Dan Akuntansi), 2025)
Introduction: This study examines the effect of tax planning, projected using the effective tax rate (ETR) and book-tax differences (BTD), on firm value in mining companies listed on the Indonesia Stock Exchange (IDX) during the 2022–2024 period.Methods: The research population consists of all mining companies listed on the IDX within the specified period. The sampling method employed is purposive sampling, resulting in a sample of 11 companies with a three-year observation period, which generates 33 data points. Data analysis was conducted using multiple linear regression analysis with SPSS version 27.Results: The findings indicate that, when examined jointly, tax planning, as projected using ETR and BTD, has a significant effect on firm value. Similarly, when analyzed individually, tax planning projected using ETR has a substantial effect on firm value. Tax planning projected using BTD also having a significant impact on firm value.Implications: These results suggest that effective tax management plays a vital role in enhancing firm value, emphasizing the importance of strategic and lawful tax planning practices within mining companies. The findings also provide policymakers with insights to design tax regulations that balance state revenue interests with corporate financial performance, particularly in highly regulated sectors such as mining. Keywords: Tax Planning, Effective Tax Rate (ETR), Book to Tax Difference (BTD), and Company Value.